Do sentiment indices impact the premium of prominent pricing factors? - Ranjeeta Sadhwani; Suresh Kumar Oad Rajput; Ume Habibah (Cogent Economics & Finance, 2018)
This study investigates whether Google Search Volume Indices (GSVIs) bring shifts in the expected return of prominent pricing factors in comparison to the Volatility Index (VIX). The results show that compared to VIX, GSVIs bring less significant changes in expected premium on Fama-French's five-factors and q-factors. Pessimistic sentiment indices (Market Crash and Bear Market) predict more significant variation in the premium of prominent pricing factors than optimistic sentiment indices (Market Rally and Bull Market), and also have a significant correlation with VIX representing downside risk. Furthermore, the sentiment indices are better in predicting premium on five-factors than q-factors.
Keywords: G12; C19; 330; VIX; Google search index; expected return; asset pricing; pricing factors